O potencial emancipatório do Programa Bolsa Família na perspectiva dos beneficiários do Município de Cerro Largo - RS - Sodre, Fabiana da Silva (2019)
The Bolsa Família Program is a public policy of direct and conditioned transfer of income, thatessentially aims to combat hunger, access to basic social services and the emancipation of families living in poverty and extreme poverty. The emancipation category finds a centrality in this research, insofar as it will be related to the Program's capacity to strengthen processes of autonomy, citizenship and development, assuming in this sense, the prediction of effective overcoming of the situations that give rise to and entitlement to the granting of benefits. This study therefore has as a central focusthe analysis and contextualization about the Bolsa Família Program as an emancipatory social policy, based on the correlation between the theoretical perspectives and the conception of the beneficiaries of the municipality of Cerro Largo -RS on the normative aspects of the Program , their understanding of limits and possibilities of overcoming situations of income deprivation and precarious access to basic social services and their capacity to reflect changes in the familiar socioeconomic context for the construction and experience of emancipation processes. It understands in this bias the theoretical-conceptual approach about emancipation in the origin and foundations of Modernity, where the individual, through the use of reason, becomes capable of exercising freedom and conquering autonomy, whereas, the senian approach presupposes freedom in its substantive and instrumental roles, as essential to the process of development, insofar as through the opportunities and social dispositions inserted in the fieldof public policy, it becomes possible to enhance human capacities. It is a qualitative research that contemplates the understanding of theoretical conceptions linked to the perspectives of the beneficiaries, in their subjective analysis about the reality in which they live, resulting in a set of reflections that involves the context of the Bolsa Família Program, for in addition to the perceptions about immediate results, in order to evidence the existence of processes of freedom, autonomy, emancipation and, therefore, development.